Are Indonesian Girls Okay? An Examination of The Discourse of Child Marriage, Victimization, and Humanitarian Visuality of Global South Girls - Annisa R Beta; Ryan Febrianto (Jurnal Studi Pemuda, 2020)
The discourse of child marriage in relation to the lives of the girls in Indonesia specifically and the Global South generally is often limited to describing their vulnerability and position as victims. Practices of child marriage are inseparable from its exploitative and harmful nature. This paper, however, shows that the discourse of child marriage produced in humanitarian projects and interventions often avoids the complexity and diversity of the practices and the lives of the girls and reduces the problem into monolithic narrative of their communities’ traditions, backwardness, and inherent gender inequality. This paper asks: How has the discourse of child marriage in relation to Indonesian girls developed historically? How have international NGOs depicted the issue of child marriage? We show that child marriage discourse is historically rooted in colonial ideas surrounding modernity, childhood, and marriage, and that documents published by international NGOs tend to flatten the complex experiences and lives of Indonesian girls.